2022
DOI: 10.3390/ijerph192113872
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Primary Care Physician Vaccination Behaviour: A Systematic Review

Abstract: Background: Vaccine hesitancy decreases adult vaccination coverage and has been recognized by WHO as a major health threat. Primary care physicians (PCP) play a key role in vaccination by giving vaccine counselling to their patients. The aim of this systematic review is to identify the knowledge, beliefs, attitudes and barriers (KBAB) associated with own vaccination and patient recommendation in primary care physicians. Methods: MEDLINE/PubMed, EMBASE and Cochrane Library databases were used to search and iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 83 publications
(65 reference statements)
0
1
0
Order By: Relevance
“…An Australian focus group study [36] revealed that a heavy GP workload and the complexity of managing patients with chronic diseases are the main GP-related barriers to SIV. Analogously, a recent systematic review of qualitative studies on vaccination [37] hesitation among health professionals highlighted the crucial role of time constraints, which are the main extrinsic factors in uencing general vaccine hesitancy. In particular, physicians often reported that the time spent on vaccination may reduce the time for other practices judged as a higher priority.…”
Section: Discussionmentioning
confidence: 99%
“…An Australian focus group study [36] revealed that a heavy GP workload and the complexity of managing patients with chronic diseases are the main GP-related barriers to SIV. Analogously, a recent systematic review of qualitative studies on vaccination [37] hesitation among health professionals highlighted the crucial role of time constraints, which are the main extrinsic factors in uencing general vaccine hesitancy. In particular, physicians often reported that the time spent on vaccination may reduce the time for other practices judged as a higher priority.…”
Section: Discussionmentioning
confidence: 99%
“…In other countries, primary care physicians, general practitioners, and family physicians also have essential roles in preventive medicine and primary care. [11][12][13] Japan is known to have strong vaccine hesitancy that is not limited to COVID-19. 14 Moreover, the burden on health care workers owing to COVID-19 treatment was substantial, and there was a severe shortage of health care workers to administer vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…Various tests for the varicella-zoster virus are utilized, including detecting IgM antibodies specific to varicella-zoster in the blood and observing multinucleated giant cells on the Tzanck smear of vesicular fluid. Additional methods involve polymerase chain reaction testing of vesicular fluid and direct fluorescent antibody testing [7][8][9][10][11].…”
Section: Herpes Zostermentioning
confidence: 99%